A South‐to‐South Cultural Adaptation of an Evidence‐Based Parenting Program for Families in the Philippines. Issue 4 (6th January 2021) - Mamauag, Bernice Landoy; Alampay, Liane Peña; Lachman, Jamie M.; Madrid, Bernadette J.; Hutchings, Judy; Ward, Catherine L.; Gardner, Frances
Abstract : Rates of child maltreatment are higher in low‐ and middle‐income countries due to risk factors such as social inequities, economic adversity, and sociocultural norms. Given the evidence showing the effectiveness of parenting interventions to prevent child maltreatment, this study embarked on a cultural adaptation of an evidence‐based parenting program with the eventual goal of integrating it within a nationwide conditional cash transfer program for low‐income Filipino parents with children aged 2–6 years. We document the systematic adaptation of the Parenting for Lifelong Health for Young Children program that was developed and tested in South Africa, for low‐resource Filipino families using the heuristic framework for the cultural adaptation of interventions. We underscore the merits of conducting a multistage top‐down and bottom‐up process that uses a participatory approach among cultural insiders and outsiders to develop a parenting intervention that reflects the contextual realities and cultural values of end users. The adapted program, Masayang Pamilya Para sa Batang Pilipino, is the product of a delicate and deliberate effort to balance Filipino childrearing goals and values with the scientific evidence on components of parenting interventions known to promote positive parenting and prevent child maltreatment. Resumen: Los índices de maltrato infantil son más altos en los países de ingresos medios y bajos debido a factores de riesgo, como las desigualdades sociales, las dificultades económicas y las normas socioculturales. Teniendo en cuenta los datos que demuestran la eficacia de las intervenciones en la crianza para prevenir el maltrato infantil, este estudio inició una adaptación cultural de un programa de crianza factual con el objetivo principal de integrarlo dentro de un programa de transferencia condicional de dinero en efectivo a nivel nacional para padres filipinos de bajos recursos con niños de entre dos y seis años. Documentamos la adaptación sistemática del programa "Crianza para una buena salud durante toda la vida" (Parenting for Lifelong Health, PLH) orientado a niños pequeños que se desarrolló y se probó en Sudáfrica, para familias filipinas de bajos recursos utilizado el marco heurístico para las adaptaciones culturales de las intervenciones. Subrayamos los méritos de llevar a cabo un proceso multietapa descendente y ascendente que emplea un método participativo entre personas conocedoras de las culturas y personas ajenas a ella para desarrollar una intervención en la crianza que refleje las realidades contextuales y los valores culturales de los usuarios finales. El programa adaptado, Masayang Pamilya Para sa Batang Pilipino, es el producto de un esfuerzo comprometido y deliberado de equilibrar los objetivos y los valores de la crianza de los niños filipinos con las pruebas científicas sobre los componentes de las intervenciones en la crianza que promueven la crianza positiva y previenen el maltrato infantil. 摘要: 由于社会不平等、经济困境和社会文化规范等风险因素，在低收入和中等收入国家里儿童受虐待的比率较高。鉴于那些能显示通过家长教育干预防止儿童虐待现象这种措施的有效性的证据, 本研究开展了以证据为基础的文化适应教育计划，其最终目的是为了将这种措施整合在一个全国性的有条件的现金转移计划中，对象为菲律宾低收入父母， 家有2 ‐ 6岁儿童。我们记录了在南非开发和测试的儿童终身健康养育(PLH)项目在资源贫乏的菲律宾家庭的适用的情况，该项目使用启发式的框架来适应干预的文化适应性。我们强调，采用由上而下和由下而上的多阶段过程，在文化内部人士和外部人士之间采用参与式方法，以发展一种反映终端用户的环境现实和文化价值的育儿干预，这些做法是有诸多好处的。经过改编的节目Masayang Pamilya Para sa Batang Pilipino是一项细致而深思熟虑的努力的成果，目的是在菲律宾的育婴目标和价值观与促进积极育儿和防止虐待儿童的育儿干预措施组成部分的科学证据两者之间实现平衡。